Exploring Project-Based Learning’s Role in the Development of Arabic Students’ Speaking Skills through Experiential Learning Theory - Gusma, Adib Julian; Yul, Widiya; Oktavera, Hasnil; Ulya, Aqil Sajidil (Mantiqu Tayr: Journal of Arabic Language, 2025)
Students of Arabic Language Education at State Institute for Islamic Studies of Kerinci often face difficulties in developing speaking skills, mainly due to traditional, teacher-centered methods that limit active participation. Project-Based Learning offers a more engaging approach, while Experiential Learning Theory helps explain how real-world learning experiences can improve students’ communicative competence. This study aims to analyze the role of Project-Based Learning in enhancing the speaking skills of Arabic language students at Kerinci through the lens of Experiential Learning Theory as developed by David Kolb. Employing a qualitative method with a case study design, the research was conducted within the context of Arabic language instruction. The study involves data collection through interviews, observations, and document analysis, followed by thematic analysis to explore the integration of Project-Based Learning and Experiential Learning Theory. The findings are interpreted using Kolb’s learning cycle to explore its role in the development of students’ Arabic speaking skills. The results show that the implementation of Project-Based Learning fosters active student participation in oral communication by creating a collaborative and reflective learning environment. In this context, Kolb’s experiential learning cycle comprising concrete experience, reflective observation, abstract conceptualization, and active experimentation was found to be organically integrated into the dynamics of the project, rendering the learning experience not only cognitively meaningful but also affectively and socially transformative. A novel contribution of this study lies in its identification of how students’ sense of ownership over the project process directly stimulates intrinsic motivation, speaking confidence, and academic resilience in the face of linguistic challenges. Furthermore, the integration of Project-Based Learning and Experiential Learning Theory was shown to promote the development of heightened metalinguistic awareness and to accelerate students’ identity shift from passive language users to active and reflective communicators. This study recommends the systematic implementation of Kolb-based Project-Based Learning within Arabic language curricula to support pedagogical transformation geared toward authentic, participatory, and sustainable communication.